2007
DOI: 10.1109/tns.2007.908459
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Auger Recombination on Charge Collection of a 6H-SiC Diode by Heavy Ions

Abstract: Charge collection efficiency (CCE) generated in a 6H-SiC p + n diode by impact of heavy ions was evaluated by the transient ion beam induced current (TIBIC) technique. Numerical analysis by using technology computer aided design (TCAD) concludes that the Auger recombination process reduces CCE. Comparing experimentally measured CCEs with calculated ones revealed that the ambipolar Auger coefficient of about 3 10 29 cm 6 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…The measured transient responses in Si PIN diodes after an ion strike with a wide variety of incident energies as shown in Fig. 1 (a) can be understood as we have suggested in previous papers [6,7]. Turning now to discuss the transient response in 6H-SiC n + p diodes after an ion strike, it is found that the slopes of transient current in 6H-SiC n + p diodes differ greatly from those in Si PIN diodes, as shown in Figs.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…The measured transient responses in Si PIN diodes after an ion strike with a wide variety of incident energies as shown in Fig. 1 (a) can be understood as we have suggested in previous papers [6,7]. Turning now to discuss the transient response in 6H-SiC n + p diodes after an ion strike, it is found that the slopes of transient current in 6H-SiC n + p diodes differ greatly from those in Si PIN diodes, as shown in Figs.…”
supporting
confidence: 57%
“…Before discussing transient response in SiC, we will here review that in Si PIN diodes. To understand the carrier dynamics in Si PIN diodes, numerical calculations using a Technology Computer Aided Design (TCAD) simulator provided by Synopsys has been carried out [6,7]. In the case of 15MeV-O, the charge collection dynamics can be simplified into the following three phases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first path with larger R c would obviously present higher impedance compared with the other two paths, thus less electrons would pass through R c and are collected by V CC eventually. On the other hand, a larger R c leads to longer discharging time and more electrons, which would have been collected by V CC and tend to annihilate via recombination with holes [15,18] because of the strong forward bias of the CS junction in the course of the multi-path discharge. For a logic inverter with load resistor R c shown in Fig.…”
Section: -4mentioning
confidence: 99%